1970
DOI: 10.3329/bja.v8i2.7018
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Gestational Diabetes Mellitus on the Mother and the Neonate – A Descriptive Study

Abstract: Context: Pregnancy complicated by diabetes is a significant medical problem not only affecting maternal health, but also jeopardizing fetal normalcy. Gestational diabetes mellitus (GDM) is a common metabolic disorder that frequently causes maternal and fetal complications. The present study was done to see the impacts of GDM on mother and neonate. Study design: Cross sectional descriptive study. Place and period of study: Department of Anatomy Chittagong Medical College, Chittagong. From May 2006 to April 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The literature provides conflicting results on Apgar scores. For example, one study found no significant difference in 1- and 5-minute Apgar scores of newborns from mothers with DM as compared to a control group ( 23 ), whereas another publication showed that placental changes consistent with reduced blood flow were associated with lower 1- and 5-minute Apgar scores ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature provides conflicting results on Apgar scores. For example, one study found no significant difference in 1- and 5-minute Apgar scores of newborns from mothers with DM as compared to a control group ( 23 ), whereas another publication showed that placental changes consistent with reduced blood flow were associated with lower 1- and 5-minute Apgar scores ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fants of diabetic mothers more frequently experience impaired breathing, whereas 48.4% of infants in our sample had respiratory disor ders re sulting from an antagonistic effect of insulin on the stimu lation of sur factant synthesis, i.e. the im paired ma turation of type II alveoli cells (21). Hypoglycemia, hypothermia, poly cy temia, cardiac insufficiency and cerebral edema caused by birth trauma and asphyxia may also induce impaired breathing (22).…”
Section: Discussionmentioning
confidence: 78%
“…Hypoglycemia, hypothermia, poly cy temia, cardiac insufficiency and cerebral edema caused by birth trauma and asphyxia may also induce impaired breathing (22). Functio nal ab nor malities of the heart were recorded in 30% of infants including interventricular septal hypertrophy and car dio myopathy, whereas cardiac insufficiency occurred in 50-10% of infants of diabetic mothers (19,21).…”
Section: Discussionmentioning
confidence: 99%